Who Gains from Buying Bad Bidders?. (31st March 2014) - Offenberg, David; Straska, Miroslava; Waller, H. Gregory
Abstract We study the value gains from takeovers of firms with poor acquisition histories. We document that the premium received by target shareholders is higher when the value loss from the targets' prior acquisitions is larger. However, the gains to target shareholders seem to be offset by losses to acquiring shareholders. The average announcement return to acquiring shareholders is negative and decreasing in the value loss from the targets' prior acquisitions. Additionally, the combined acquirer-target value created in these takeovers is insignificant. These results suggest that the value lost from targets' prior acquisitions is not recovered through changes in corporate control.